Expository Teaching in Digital Spaces: A Case Study of the Adi Hidayat Official YouTube Channel - Pangesti, Zunita Lut Fiana; Zaini, Muhamad; Amalia, Rosyida (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This research aims to explore the implementation of expository learning strategies on the YouTube channel